Reducing racial and ethnic disproportionality in school discipline through an assessment‐to‐intervention process: A framework and process. Issue 12 (1st February 2022) - Pullmann, Michael D.; Gaias, Larissa M.; Duong, Mylien T.; Gill, Tara; Curry, Caryn; Cicchetti, Colleen; Raviv, Tali; Kiche, Sharon; Cook, Clayton R.
Abstract: Racial and ethnic disproportionality in discipline (REDD) represents a longstanding and pervasive issue in the United States educational system. However, researchers and interventionists have not sufficiently provided educators with appropriate frameworks and feasible tools to disrupt REDD and promote equity. The goal of this paper is to present a framework of eight malleable factors associated with REDD and describe the Disproportionality in Discipline Assessment for Schools (DDAS). The DDAS is a suite of user‐friendly tools based on this framework, designed to help school teams identify and address REDD. Two studies are described. Study 1 presents the results of educator feedback on a presentation of the framework and the DDAS in terms of their perception of its feasibility, usability, and validity/logical soundness. Study 2 presents the process of applying the DDAS in four real‐world school settings. Results indicated that the framework and the DDAS were useful and feasible tools to help schools increase equity and address REDD. Modifications to the framework and the DDAS were made to improve validity and appropriateness. Highlights: The Disproportionality in Discipline Assessment for Schools (DDAS) is a suite of tools to help schools achieve more equitable discipline. Focus groups and a pilot study with educators found the DDAS useful and feasible.